Convective boundary layer flow of Jeffrey fluid and Jeffrey nanofluid over various geometry - Syazwani, Mohd Zokri (2019)
Non-Newtonian Jeffrey fluid model describes the viscoelastic property that elucidates the dual components of relaxation and retardation times. High shear viscosity, shear thinning and yield stress are the important features of this fluid model, which is profoundly relevant with the polymer industry. The advantage of Jeffrey fluid is that it can be reduced to Newtonian fluid at very high wall shear stress, provided that the wall shear stress is much greater than the yield stress. Owing to these reasons, the proposed study herein aims to examine the mathematical models for forced, free and mixed convection flows of Jeffrey fluid. Flow that is induced by various surfaces such as stretching sheet, inclined stretching sheet and horizontal circular cylinder under the absence or presence of nanoparticles is considered. The flow analysis for nanoparticles is performed based on the Buongiorno model. Specific problems are studied with several effects including viscous dissipation, magnetohydrodynamic and thermal radiation. Mathematical formulation starts with the transformation of dimensional governing equations into dimensionless form using the appropriate non-dimensional variables. Similarity or non-similarity transformation variables are applied to reduce the respective number of dependent or independent variables. The resulting ordinary or partial differential equations are then solved numerically via the implicit finite difference scheme, namely the Keller-box method. Numerical algorithm is developed in MATLAB software to obtain the numerical solutions. Authentication of the numerical results is achieved through comparison with the results available in the existing literature. The numerical results of velocity, temperature and concentration profiles as well as skin friction coefficient, Nusselt and Sherwood numbers for ratio of relaxation to retardation times, Deborah number, mixed convection parameter, Prandtl number, Eckert number, concentration buoyancy parameter, Brownian motion, thermophoresis diffusion parameter and Lewis number are presented graphically and analysed in details. Findings disclose that, the contradictory behaviours of both Jeffrey fluid parameters are observed over the specified distributions, regardless of the surface geometry under consideration. The presence of nanoparticles in Jeffrey fluid has enhanced the temperature profiles and consequently enhanced the heat transfer. Flow passing through the horizontal circular cylinder reveals that the boundary layer separation for Jeffrey nanofluid is more delayed than the Jeffrey fluid for dissimilar mixed convection parameter. Delaying the boundary layer separation up to the end of the cylinder surface can greatly reduce drag. This separation is usually undesirable in engineering applications because considerable amount of energy is lost in the process of eddying.